Open approaches for cruciate ligament reconstruction in knee dislocations: A technical note and case series - Held, Michael (SICOT J, 2021)
Introduction: Arthroscopic surgery is the gold standard for cruciate ligament reconstruction in multi-ligament knee injuries. However, hospitals in limited-resource settings often lack arthroscopic-trained surgeons or equipment. Open approaches for treating knee dislocations can overcome many of these limitations. Methodology: This study aims to describe techniques for open approaches in a supine patient to address the cruciate ligaments in multi-ligament knee injuries and to review associated complications and clinical outcomes in a retrospective case series. Results: Ten patients with multi-ligament knee injuries who had undergone open cruciate ligament reconstruction between July 2016 and November 2018 were retrospectively identified. Open approaches were performed owing to the extravasation of arthroscopy fluid into the posterior compartment (3) or a large traumatic arthrotomy (7). Complications and patient-reported outcomes were analysed. Eight of the 10 patients were followed up at 10 months postoperatively (range, 5–23 months). None had iatrogenic neurovascular damage. Median outcomes scores were: visual analogue scale, 45 (range, 0–100); Knee Injury and Osteoarthritis Outcome Score-Physical Function Short Form, 81.4 (range, 75–100); Lysholm, 85 (range, 67–92). Discussion: Open approaches were safe and useful in treating cruciate ligaments and should be considered in arthroscopy fluid extraversion and large traumatic arthrotomies.